2003
DOI: 10.1038/sj.jp.7210847
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Substance Abuse Intervention in Obstetric Clinics Decreases Adverse Neonatal Outcomes

Abstract: Improved neonatal outcomes were found among babies whose mothers received substance abuse treatment integrated with prenatal care. The babies of SAT women did as well as control infants on rates of assisted ventilation, low birth weight, and preterm delivery. They had lower rates of these three neonatal outcomes than infants of either SA or S women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 33 publications
1
56
0
Order By: Relevance
“…12 Initial research on Early Start demonstrated that pregnant women who were screened positive, assessed and treated for substance abuse problems by Early Start had neonatal outcome rates for assisted ventilation, preterm delivery and low birth weight similar to control women, and significantly lower than substance abusers who were screened positive only or screened positive and assessed but not treated. 13 The purpose of this study, which looked over a longer time period and at maternal outcomes not included in the original study, was to provide a more comprehensive evaluation of Early Start on maternal and neonatal outcomes to support this becoming the standard of care for all prenatal clinics and establish the program as a gold standard for replication.…”
Section: Introductionmentioning
confidence: 99%
“…12 Initial research on Early Start demonstrated that pregnant women who were screened positive, assessed and treated for substance abuse problems by Early Start had neonatal outcome rates for assisted ventilation, preterm delivery and low birth weight similar to control women, and significantly lower than substance abusers who were screened positive only or screened positive and assessed but not treated. 13 The purpose of this study, which looked over a longer time period and at maternal outcomes not included in the original study, was to provide a more comprehensive evaluation of Early Start on maternal and neonatal outcomes to support this becoming the standard of care for all prenatal clinics and establish the program as a gold standard for replication.…”
Section: Introductionmentioning
confidence: 99%
“…25 A study of 6774 pregnant women receiving prenatal care through Kaiser Permanente Managed Care Plan demonstrated that pregnant women, who screened positive for alcohol and other drug use and received even a single brief intervention had a reduced rate of low birth weight infants, preterm infants and infants who required ventilation. 26 Identification of the lighter drinker takes on added importance in that research into the effects of alcohol as a teratogen have revealed that even low doses of alcohol may have serious long-term consequences for children. 18,27 Over the last few years, physicians' attitudes toward intervening in their patients' drug and alcohol problems have become more positive, 28 and the American College of Obstetricians and Gynecologists recently stated that obstetricians are ethically obligated to address substance use as a part of routine prenatal care with all patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, a recent study at Kaiser Permanente Medical Care Program documented the cost savings accrued when pregnant substance using women are identified early in pregnancy and provided substance abuse interventions. 3 A highly sensitive screening instrument addresses the need to identify all women at risk. It identifies not only those pregnant women who are drinking heavily or whose drug use is at a high enough level to impair daily functioning, but also identifies those women whose pregnancies are at risk from tobacco use as well as relatively small amounts of alcohol, marijuana or other drugs.…”
Section: Significancementioning
confidence: 99%
“…A number of studies have found poor pregnancy and neonatal outcomes among women who used alcohol or illegal drugs during pregnancy, [1][2][3][4] and the long-term impact of prenatal alcohol or illicit drug exposure on the development and behavior of the exposed child [5][6][7][8] is now being documented. However, despite the concern over the consequences of prenatal exposure to alcohol and other drugs, substance use by the pregnant woman remains a frequently missed diagnosis.…”
Section: Introductionmentioning
confidence: 99%